Financial analysis: the extent of its impact on property stock prices listed in KLSE / Ahmad Hanazir Abdul Halim - Abdul Halim, Ahmad Hanazir (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 1995)
The research was carried out to identify the influence of companies' financial analysis towards stock prices. The research covered 8 property companies listed in KLSE for 5 year period (1988-1992). Data were obtained from companies' annual reports and KLSE publications. Methodology used were Financial Analysis and Stastistical Analysis. The result of the research revealed that financial standing of a company has a significant impact on its stock price. Therefore, it can be used as a determinant factor of stock price. The research was also successfully measured the extent of financial analysis impact on stock price.